Budaya Pamali dan Strategi Penerapan Pola Asuh Berkesadaran - Indrayani, Rusmiati; Al-Mubarak, Ahmad Munir (STKIP PGRI SITUBONDO, 2024)
The purpose of this study is to describe the strategy of implementing conscious parenting in forming an understanding of taboo culture. This study uses a mixed method or a combination of quantitative and qualitative methods. The number of respondents/research informants is 100 people. The determination of respondents uses a purposive sampling technique. The results of the study, as many as 85% of the old generation of the Banjar tribe still believe in taboos and prohibitions as a form of local wisdom. The types of taboos are divided into three parts, customary taboos (60%), natural taboos (10%), and taboos in social interaction (20%). The strategy of inheriting values in the form of advice and examples is integrated through parenting. The combination of the application of authoritarian, authoritative, and laizs faire parenting patterns forms a conscious parenting pattern. As many as 75% of respondents acknowledge the important role of the older generation such as grandparents, fathers and mothers as guardians of cultural identity.